Wireless Sensor Network For Landslide Assessment (International Journal of Engineering and Computer Science, 2014)
Natural disasters are increasing worldwide due to the global warming and climate change. We are focusing on Landslides disaster.  However, this disaster is largely unpredictable and occurs within very short spans of time. Therefore technology has to be developed to capture relevant signals with minimum monitoring delay. Wireless Sensors are one of the cutting edge technologies that can quickly respond to rapid changes of data and send the sensed data to a data analysis centre in areas where cabling is inappropriate.  The heart of this project lies with the use of a GSM + Zigbee + Sensor. Every sensor has Zigbee Tx mounted on it. When landslides happens sensor sense that and transfer data through router to the coordinator. Coordinator has GSM + Zigbee Rx. Coordinator receives it and this information is transmitted by GSM to the Control centre. GSM in the Control centre receives this and transfer this information via GSM to rescue team. We also check the status of sensor by sending message. Monitoring Landslides is very helpful to protect people and avoid accident. Because of landslides many accident occur on highway, hill station and railway track. So with the help of this system we can warn the main centre about where the landslides happen. We also check the status of tunnels and landslides prone area.